UPAYA PENCEGAHAN STUNTING MELALUI OPTIMALISASI PENGOLAHAN PRODUK LOKAL SEBAGAI SUMBER NUTRISI BALITA - Qisma Ziyan Farkha; Ries Dyah Fitriyah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This research explores efforts to overcome stunting in Probolinggo Regency, East Java, which has a stunting prevalence of 12.97% in 2023. Research in Banyuanyar Kidul Village focuses on socialization and demonstration of making MPASI from corn, as a local village asset. Involving 145 mothers and toddlers from four posyandu. This outreach activity is a form of education and demonstration carried out with the theme "Efforts to Prevent Stunting Through Optimizing the Processing of Local Products as a Source of Nutrition for Toddlers". Research conducted on the Posyandu Mothers group in Banyuanyar Kidul Village used the Asset Based Community Development (ABCD) approach. The Assed Based Community Development (ABCD) approach is a sustainable development approach that focuses on the assets, strengths and potential of the community. The aim of this activity is to provide knowledge for mothers of toddlers about stunting and help mothers of toddlers know the benefits of local food assets such as corn which can be processed into MPASI. The results show an increase in mothers' knowledge about corn nutrition and how to process it into corn pudding as well as mothers' enthusiasm in practicing the recipe. This program has succeeded in providing education on the importance of nutrition and its use.